Contrast Medium Hypersensitivity: A Large Italian Study with Long-Term Follow-Up - Eleonora Nucera; Giuseppe Parrinello; Sebastiano Gangemi; Alessandro Buonomo; Arianna Aruanno; Franziska Michaela Lohmeyer; Riccardo Inchingolo; Angela Rizzi (Biomedicines, 2022)
Hypersensitivity reactions (HRs) to contrast media (CM) are a major problem. We compared differences of HRs to iodinated contrast media (ICM) versus gadolinium-based contrast media (GBCM), collecting data on prevalence, type, latency and severity. Secondly, the predisposition to perform new contrast tests, use of premedication and possible appearance of new reactions were explored in a long-term follow-up of 5 years. Clinical data, comorbidities, skin test (ST) results, re-exposure to CM procedures with any new reactions, premedication and CM used were collected. In a retrospective single-center study, 350 patients with mild to moderate HRs were enrolled. Asthma, food allergy, non-allergic drug hypersensitivity and neurologic disease were significantly more frequent in patients with HRs to GBCM compared to the high evidence of cardiovascular disease and history of cancer in patients with HRs to ICM. A marked delay in performing STs was reported by patients with negative results (66 months, p < 0.01). Iomeprol, iopamidol and gadobenic acid were the culprit CM most involved in HRs in patients with positive STs. During follow-up, 7.1% of responders reported new HRs to CM despite negative STs, premedication and infusion of alternative CM in most cases.